Discovery and Optimization of Ergosterol Peroxide Derivatives as Novel Glutaminase 1 Inhibitors for the Treatment of Triple-Negative Breast Cancer - Ran Luo; Haoyi Zhao; Siqi Deng; Jiale Wu; Haijun Wang; Xiaoshan Guo; Cuicui Han; Wenkang Ren; Yinglong Han; Jianwen Zhou; Yu Lin; Ming Bu (Molecules)
In this study, novel ergosterol peroxide (EP) derivatives were synthesized and evaluated to assess their antiproliferative activity against four human cancer cell lines (A549, HepG2, MCF-7, and MDA-MB-231). Compound 3g exhibited the most potent antiproliferative activity, with an IC50 value of 3.20 µM against MDA-MB-231. This value was 5.4-fold higher than that of the parental EP. Bioassay optimization further identified 3g as a novel glutaminase 1 (GLS1) inhibitor (IC50 = 3.77 µM). In MDA-MB-231 cells, 3g reduced the cellular glutamate levels by blocking the glutamine hydrolysis pathway, which triggered reactive oxygen species production and induced caspase-dependent apoptosis. Molecular docking indicated that 3g interacts with the reaction site of the variable binding pocket by forming multiple interactions with GLS1. In a mouse model of breast cancer, 3g showed remarkable therapeutic effects at a dose of 50 mg/kg, with no apparent toxicity. Based on these results, 3g could be further evaluated as a novel GLS1 inhibitor for triple-negative breast cancer (TNBC) therapy.